Evaluation of fire lookout towers using GIS-based spatial visibility and suitability analyzes Procjena tornjeva za nadzor požara pomoću analize prostorne vidljivosti i prikladnosti potpomognute GIS-om - Akay, Abdullah Emin; Wing, Michael; Büyüksakalli, Halit; Malkoçoglu, Salih (2020)
Effective forest fire fighting involves alerting firefighting teams immediately in the case of a fire so that teams can promptly arrive the fire scene. The most effective way for an early detection of forest fires is monitoring of forest lands from fire lookout towers. Especially in fire sensitive forest lands, towers should be systematically located in such a way that fire lookout personnel can monitor the largest amount of forest land as possible. In this study, the visibility capabilities of lookout towers located in Köyceğiz Forest Enterprise Directorate (FED)in the city of Muğla in Turkey were evaluated by using Geographical Information System (GIS) based visibility and suitability analysis. The results of visibility analysis indicated that 77.12% of forest land were visible from the current towers. To extend the proportion of visible forest lands, locations of additional lookout towers were evaluated using spatial visibility and suitability analysis in which the tower locations were examined by considering specific criteria (i.e. distance to roads, elevation, ground slope, topographic features). Suitability analysis results identified five new towers in addition to current towers in the study area. The results indicated that visible forest lands increased to 81.47% by locating new towers, and increase of almost 4.35%. In addition, over half of the forests became visible by at least two towers when including five towers suggested by suitability analysis. The GIS-based method developed in this study can assist fire managers to determine the optimal locations for fire lookout towers for effective fire management activities.
Učinkovito suzbijanje šumskih požara uključuje trenutno uzbunjivanje protupožarnih timova u slučaju požara kako bi mogli na vrijeme stići na mjesto požara. Najučinkovitiji način ranog uočavanja šumskog požara je nadzor šumskih područja s tornjeva za nadzor požara. Tornjevi bi trebali biti sustavno smješteni na način da osoblje za nadzor može nadzirati najveću moguću površinu šume, osobito u ugroženijim šumskim predjelima. U ovom su istraživanju procijenjene mogućnosti promatranja tornjeva za nadzor smještenih u šumariji Köyceğiz, u gradu Muğla u Turskoj pomoću analize vidljivosti i prikladnosti potpomognutom Geografskim informacijskim sustavom (GIS). Rezultati analize vidljivosti pokazali su da je 77,12 % šumskog područja vidljivo sa sadašnjih tornjeva. Kako bi se povećao udio vidljivoga šumskog područja, lokacije dodatnih tornjeva za nadzor procijenjene su pomoću analize prostorne vidljivosti i prikladnosti u kojoj su lokacije tornjeva ispitane razmatrajući specifične kriterije (npr. udaljenost od cesta, visina, nagib terena, topografske karakteristike). Rezultati analize prikladnosti identificirali su pet novih tornjeva uz sadašnje tornjeve na promatranome području. Rezultati su pokazali da bi se dodavanjem novih tornjeva vidljiva šumska površina povećala na 81,47 %, što je povećanje od gotovo 4,35 %. Uz to, analiza prikladnosti pokazala je da bi preko polovice šume bilo vidljivo s najmanje dva tornja kada bi se dodalo ovih pet tornjeva. Metoda potpomognuta GIS-om razvijena u ovome istraživanju može pomoći upraviteljima za zaštitu od požara da odrede optimalne lokacije za tornjeve za nadzor požara u svrhu učinkovitih protupožarnih aktivnosti.
Bibliografija: str. 287-288
Summary ; Sažetak.
Keywords: Šumski požari -- Tornjevi za nadzor -- Protupožarna zaštita -- Analiza vidljivosti -- GIS -- Geografski informacijski sustavi